The Rosie-Project : novel - Simsion, Graeme (London : Penguin UK, 2014)
"A world so original, in a story so compelling, I defy you not to read through the night. Read this glorious novel now, in the moment, where it lives." (Adriana Trigiani, bestselling author of The Shoemaker's Wife)
In englischer Sprache